1987
DOI: 10.1017/s0033291700013118
|View full text |Cite
|
Sign up to set email alerts
|

A community mental health survey in Cantabria: a general description of morbidity

Abstract: SynopsisA two-stage mental illness survey of a random sample of persons aged 17 years and over from a rural community in Cantabria, Spain, is described. In the first stage newly qualified doctors and final year medical students interviewed 1223 respondents (583 males and 640 females) at their homes, using the General Health Questionnaire (GHQ-60) and other psychopathological and social questionnaires. In the second stage senior psychiatrists carried out an at-home interview on a sample composed of all those wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
3
6

Year Published

1995
1995
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(52 citation statements)
references
References 29 publications
6
37
3
6
Order By: Relevance
“…The 1-month prevalence found in the 1993 study is markedly lower than the estimates reported by other studies that used PSE-CATEGO [4, 6, 20, 21], although it is identical to that found in Nijmegen, The Netherlands (7.3%) [23]. Similar rates have also recently been reported in Northern Ireland (7.5%) [22] and central Manchester (8.6%) [24]; both of these studies were conducted using the standard SCAN interview [25], which, however, incorporates the questions and the principles of PSE-IX.…”
Section: Discussioncontrasting
confidence: 64%
“…The 1-month prevalence found in the 1993 study is markedly lower than the estimates reported by other studies that used PSE-CATEGO [4, 6, 20, 21], although it is identical to that found in Nijmegen, The Netherlands (7.3%) [23]. Similar rates have also recently been reported in Northern Ireland (7.5%) [22] and central Manchester (8.6%) [24]; both of these studies were conducted using the standard SCAN interview [25], which, however, incorporates the questions and the principles of PSE-IX.…”
Section: Discussioncontrasting
confidence: 64%
“…Spain does not have a national registry that would make it possible to know the exact number of individuals with schizophrenia, although two regional studies estimate the prevalence at 0.6-0.8 for the adult population (17 years of age and older) [32,44]. In general the prevalence figures for schizophrenia are very similar across countries and regions, which means that the evident differences in rates are due more to underdiagnosis than to real epidemiological differences.…”
Section: The Costs Of Schizophrenia In Spain Original Papersmentioning
confidence: 99%
“…By combining this information with the data included in the EDDES and estimating a prevalence rate of schizophrenia in Spain of 0.8 of the adult population [32,44] we estimated that 141.1 million hours of care are attributable to schizophrenia. This amount of care time when translated into monetary terms equals €926.3 million.…”
Section: Direct Nonmedical Costs (Informal Costs)mentioning
confidence: 99%
“…However, marital status has different associations with effective disorder in different cultures. Married women are at low risk of disorder in Mediterranean countries (Mavreas et al 1986 ;Va! zquez-Barquero et al 1987), in rural New Zealand (Romans-Clarkson et al 1988) and in British orthodox Jews (Loewenthal et al 1995).…”
Section: High Risk Groupsmentioning
confidence: 99%